Memoirs of a polar bear - Tawada, Yoko, 1960- (New Directions Publishing Corporation, 2016)
"The Memoirs of a Polar Bear is a novel that stars three generations of talented writers and performers who happen to be polar bears. The Memoirs of a Polar Bear has in spades what Rivka Galchen hailed in The New Yorker as "Yoko Tawada's magnificent strangeness"--Tawada is an author like no other. Three generations (grandmother, mother, son) of polar bears are famous, both as circus performers and writers in East Germany: they are polar bears who move in human society, stars of the ring and of the literary world. In Chapter One, the grandmother matriarch in the Soviet Union accidentally writes a bestselling autobiography. In Chapter Two, Tosca, her daughter (born in Canada, where her mother had emigrated) moves to the DDR and takes a job in the circus. Her son--the last of their line--is Knut, born in Chapter Three in a Leipzig zoo, but raised by a human keeper in relatively happy circumstances in the Berlin zoo, until his keeper, Matthias, is taken away... Happy or sad, each bear writes a story, enjoying both celebrity and "the intimacy of being alone with my pen.""--